Fire suppression makes wildfires more severe and accentuates impacts of climate change and fuel accumulation - Kreider, Mark R.; Higuera, Philip E.; Parks, Sean A.; Rice, William L.; White, Nadia; Larson, Andrew J. (Nature communications, 2024)
Fire suppression is the primary management response to wildfires in many areas globally. By removing less-extreme wildfires, this approach ensures that remaining wildfires burn under more extreme conditions. Here, we term this the “suppression bias” and use a simulation model to highlight how this bias fundamentally impacts wildfire activity, independent of fuel accumulation and climate change. We illustrate how attempting to suppress all wildfires necessarily means that fires will burn with more severe and less diverse ecological impacts, with burned area increasing at faster rates than expected from fuel accumulation or climate change. Over a human lifespan, the modeled impacts of the suppression bias exceed those from fuel accumulation or climate change alone, suggesting that suppression may exert a significant and underappreciated influence on patterns of fire globally. Managing wildfires to safely burn under low and moderate conditions is thus a critical tool to address the growing wildfire crisis. Fire suppression removes less-extreme wildfires, concentrating fires under extreme conditions. The authors use model simulations to show how this “suppression bias” intensifies fire behavior and effects, beyond fuel accumulation and climate change impacts.